2015
DOI: 10.1097/mrr.0000000000000085
|View full text |Cite
|
Sign up to set email alerts
|

Social and community participation following spinal cord injury

Abstract: Evaluation of rehabilitation outcomes following acquired disability should include participation in social and community life. Evidence is needed to guide clinical practice to ensure that it is client-centered; therefore, findings from studies that report on social and community participation following spinal cord injury (SCI) need to be reviewed and synthesized. The objectives of this critical literature review are to examine the available evidence on social and community participation following SCI and to ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
94
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(97 citation statements)
references
References 37 publications
0
94
0
3
Order By: Relevance
“…impairment or functioning level) to the impact environmental and personal factors, as well as participation and activity can have on one's health and quality of life. 6,7 Participation ("a person's involvement in a life situation") 8 strongly related to quality of life 9 has emerged as an important clinical outcome with the SCI population. 6 Furthermore, social participation as a subset of participation is defined as engagement in activities that entail social interactions with others within the community and outside the home environment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…impairment or functioning level) to the impact environmental and personal factors, as well as participation and activity can have on one's health and quality of life. 6,7 Participation ("a person's involvement in a life situation") 8 strongly related to quality of life 9 has emerged as an important clinical outcome with the SCI population. 6 Furthermore, social participation as a subset of participation is defined as engagement in activities that entail social interactions with others within the community and outside the home environment.…”
Section: Introductionmentioning
confidence: 99%
“…6,7 Participation ("a person's involvement in a life situation") 8 strongly related to quality of life 9 has emerged as an important clinical outcome with the SCI population. 6 Furthermore, social participation as a subset of participation is defined as engagement in activities that entail social interactions with others within the community and outside the home environment. 10 In recent years, the influence of the ICF on investigating and treating individuals with SCI from a different perspective has advanced the treatment and management of secondary conditions.…”
Section: Introductionmentioning
confidence: 99%
“…But references of Pelletier [34] presented data does not correspond to our study results, which suggest that at the end medical rehabilitation period decreased the participation in recreation and leisure activities and in subsequent periods remained at the same level. However, authors [20,35] participation and engagement in sports and recreational activities increased with every year after SCI onset, and too low participation in these activities related to the limited opportunities of people with disabilities in sports and employment, especially in smaller towns. Therefore, the authors claim that the even during inpatient rehabilitation, it is important to start encourage people after SCI participation in sport and active leisure, by engaging in nongovernmental, and employment of the disabled sports organizations.…”
Section: Discussionmentioning
confidence: 99%
“…Mostly during inpatient rehabilitation for assessing rehabilitation outcomes and effectiveness were used mobility and daily activities assessing [2,3,17], but none of them can be considered as a standard and none of them covers all aspects of functioning and physical activity in long-term context [4,18,19]. It is very important comprehensively assess functioning and disability, to identify the prototypical spectrum of functional problems associated with personal daily and social life, occupations and activities issues that people with SCI could experience in real life after rehabilitation in 1, 5, 10 and more years [10,20].…”
Section: Introductionmentioning
confidence: 99%
“…27 Prior research with the SCI population has indicated that participation in life activities, when included in community-based rehabilitation, has a direct influence on physical and psychosocial clinical outcomes. 28,29 Yet, it is still unclear what aspects of community and social participation within the realm of the ICF actually have a significant impact on the overall health of this population. 29 Although the literature has examined QOL in people with SCI, few studies have examined how perception of health impacts participation and autonomy for this population.…”
mentioning
confidence: 99%